Memory and dehumanization in Jorge Semprún´s Concentrationary Narrative - Sánchez Zapatero, Javier (Hispania Nova, 2019)
Prisoners in Nazi concentration camps suffered a similar process of progressive and continuous dehumanization, even when they were imprisoned in different geographical places. Prisoners were deprived of the civilizing atmosphere where they lived before the arrest, and their bodies became entities whose only goal was survival. This paper approaches Jorge Semprún´s works from the perspective of the dehumanizing process suffered by the survivors, and the way their life experience was reduced to the physical survival of the body. It includes an inventory of Semprún´s autobiographical experiences, with the purpose of expressing the impossibility to verbalize the experience in concentration camps.
Keywords: Jorge Semprún; Concentration Camps; Concentrationary Narrative; Dehumanization; Ineffability